Usos e repercussões de resultados do SARESP na opinião de professores da rede estadual paulista - Rodrigues, Rodrigo Ferreira (2011)
This study aimed to identify, in the opinion of teachers, possible repercussions in the daily classroom according to the results obtained from the System Evaluation of Educational Achievement of São Paulo (SARESP). We seek to identify and analyze changes in practices of teachers who would result from implementation of SARESP. We chose qualitative research in order to understand the phenomenon in the context of pedagogical practice and its manifestations, from the description to analyze and interpret the manifest meanings evident in responses to the questionnaires. We chose to select only language teachers of Portuguese and Mathematics, who teach at the final grades of elementary school and High school, the state public school teachers and with five or more years of teaching, thus reaching a total of 16 teachers from various regions, school units and realities of the city of São Paulo. The questionnaires were organized under three axes of analysis: axis 1: identify what teachers know about and SARESP and the Education Development Index of the State of São Paulo (IDESP); axis 2: explained the opinion of teachers on the network deployment and SARESP and IDESP; axis 3: identified the possible impact on the practice of teachers surveyed by deploying SARESP and IDESP. Studies show that the use of SARESP by schools and teachers tends to favor the teaching plan and curriculum, however, that there is a dearth of research that reflects on the use SARESP results of the daily classroom in the opinion of teachers. The evaluation of system can be an ally, if it can be reflected, committed to the subjects, their contexts and pathways, providing tools for the assessment, development and learning